A permeation model of shale gas in cylindrical-like kerogen pores at geological conditions. (2nd November 2019) - Sun, Jingjing; Liu, Zhiping; Cao, Dapeng
Graphical abstract: Highlights: The permeation behavior of shale gas in cylindrical-like kerogen pores is investigated by using DCV-GCMD method. The effects of temperature, pressure and pore size on the permeability of shale gas at geological conditions are explored. A new permeation model is proposed to describe the permeation behavior of shale gas in cylindrical-like kerogen pores. Abstract: Understanding the diffusion and permeation behavior of shale gas at geological depths is significantly important to exploration of shale gas, while the permeation mechanism of shale gas in shale gas reservoir is closely related to the confined fluid behavior at mesoscopic scale and cannot be described by traditional Fick or Knudsen diffusion models. In this work, we use the dual control volume grand canonical molecular dynamics method to systematically investigate the permeation processes of shale gas in cylindrical -like kerogen pores represented by the carbon nanotube at different geological depths, and hundreds of simulation data in different pressures, temperatures and pore diameter are obtained. By analyzing these simulated data, we propose a new permeation model to describe the permeability of shale gas in cylindrical-like kerogen pores at geological depths. The new model can satisfactorily reproduce the extrapolation testing data of permeability of shale gas, and perfectly bridge the gap between macroscopic Fick model and microscopic Knudsen model, which provides a useful guidance and reference for exploration of shale gas.